Manual de Política Normativa Para una Institución de Educación a Distancia (2017)
In educational institutions that offer programs under any form of education, it is necessary to analyze, design, develop, implement and evaluate a normative policy manual that allows for the assurance of the educational quality imparted. This literary review presents basic criteria to be considered by an Institution of Distance Education (IDE) in terms of the generalities, conditions and components of the philosophical, legal, fiscal, geographical and academic, administrative and Financial, technological, professorial and student that constitute the normative policy manual. Some references are presented as an annex in relation to the normative policy for Colombia, which, with its mandatory application, makes it possible to guarantee the provision of a high quality service by educational institutions.